Hazy Bloom and the pet project - Hamburg, Jennifer (Hamburg, Jennifer. Hazy Bloom., 2018)
"Hazel 'Hazy' Bloom uses her tomorrow power--her ability to see visions of things that happen one day in the future--to try to convince her parents she's ready for a pet iguana"--